The Geopolitical Conditions Of The Emergence Of The Democratic Republic Of Azerbaijan (1918): A Brief Overview - Harutyunyan, Anush (ՀՀ ԳԱԱ)
Two Russian revolutions of 1917 were the turning points that shaped the development of Transcaucasia leading first to the separation of the region from Russia and then to the emergence of three independent states: Armenia, Georgia and Azerbaijan. However, it was not only revolutionary processes within Russia and the ensuing civil war that determined the independence of the Transcaucasia, but also the clash and combination of interests of a number of regional and extra-regional states։ Ottoman Empire, German Empire, Great Britain, Soviet power, and White army in Southern Russia. The main goal of this research is to reveal the combination of those geopolitical conditions, which led to the creation of a new state called “Azerbaijan” in the Eastern Transcaucasia. In the article are examined the following issues: the political approaches of Muslims, the Caucasian invasion of Turkish army and the declaration of Azerbaijan’s independence, Baku as a key to real independence or destruction. Overall, it is important to discuss the purpose and legality of naming the newly formed state after the historical name of the territory that is a constituent part of another state.
Keywords: History